2009
DOI: 10.1002/jor.20955
|View full text |Cite
|
Sign up to set email alerts
|

Absence of beta3 integrin accelerates early skeletal repair

Abstract: Integrins are heterodimeric transmembrane proteins that mediate cell-matrix interactions and modulate cell behavior. Beta3 subunit is a component of aIIb3 and aVb3 integrins. In this study, we first determined that b3 transcripts are expressed by cells within fracture calluses at 7 and 10 days after injury in a mouse model. We then analyzed fracture healing in mice deficient of b3 integrin with molecular, histomorphometric, and biomechanical techniques. We found that lack of b3 integrin results in an extended … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Therefore, healing of an injured tissue usually leads to the formation of a tissue that differs in morphology or function from the original tissue. This type of healing is called “repair.” Although, it may contain similar environmental cues that lead the osteogenic process, the spatial and temporal dynamics of the molecules may lean toward a delayed or altered healing 42‐45 . Tissue “regeneration,” however, is a term used to describe a healing process that leads to complete restoration of morphology and function.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, healing of an injured tissue usually leads to the formation of a tissue that differs in morphology or function from the original tissue. This type of healing is called “repair.” Although, it may contain similar environmental cues that lead the osteogenic process, the spatial and temporal dynamics of the molecules may lean toward a delayed or altered healing 42‐45 . Tissue “regeneration,” however, is a term used to describe a healing process that leads to complete restoration of morphology and function.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that α1β1 regulates callus growth through the control of skeletal progenitor proliferation and cartilage matrix production. In contrast, the early phase of fracture healing was accelerated upon the loss of integrin β3 (Hu et al, ). β3‐null mice had increased bleeding time, significantly more new bone and cartilage tissues at seven days of post‐fracturing, while they exhibited no apparent changes at later stages compared with control animals.…”
Section: Bone Formation and Functionmentioning
confidence: 99%
“…A murine osteoblastic cell line made to overexpress human αvβ3 showed an increase in proliferation rate but a decrease in matrix mineralization 66. Furthermore, early fracture healing was accelerated in the tibiae of β3‐null mice, and 23 genes related to osteogenesis were upregulated at least two‐fold in the β3‐null mice 67. The αvβ3 integrin is also the major integrin receptor expressed by osteoclasts68 and plays a major role in osteoclast adhesion,69 resorption,70 and sealing zone organization 71…”
Section: Bone Ecm Composition and Key Integrins Implicated In Osteogementioning
confidence: 99%
“…66 Furthermore, early fracture healing was accelerated in the tibiae of b3-null mice, and 23 genes related to osteogenesis were upregulated at least two-fold in the b3-null mice. 67 The avb3 integrin is also the major integrin receptor expressed by osteoclasts 68 and plays a major role in osteoclast adhesion, 69 resorption, 70 and sealing zone organization. 71 Targeting materials to integrins such as a2b1 and a5b1, which are expressed by osteoblasts-like cells and regulate osteogenesis while preventing interactions with integrins that may inhibit osteoblastic differentiation such as avb3, may be a powerful molecular strategy for developing improved orthopedic biomaterials.…”
Section: B1 Integrinsmentioning
confidence: 99%
See 1 more Smart Citation